2019
DOI: 10.17219/acem/94139
|View full text |Cite
|
Sign up to set email alerts
|

The role of toll-like receptors in multifactorial mechanisms of early and late renal allotransplant injury, with a focus on the TLR4 receptor and mononuclear cells

Abstract: Krajewska M. The role of toll-like receptors in multifactorial mechanisms of early and late renal allotransplant injury, with a focus on the TLR4 receptor and mononuclear cells. AbstractThe innate immune system is activated before an adaptive immune response. An expression of a particular toll-like receptor (TLR) in a transplanted kidney depends on the localization of specific cells (e.g., endothelium, elements of the nephron structure), recent pathology and the time passed since transplantation. The TLR4 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The MAPK pathway is a key factor in regulating cisplatin-induced kidney damage and inflammation. Based on previous evidence, various biological responses have been associated with the activation of MAPKs, which can activate the MAPK pathway by producing oxidative stress and TNF-α in the kidney tissues [40]. In this study, we showed that there was an increased amount of the phosphorylated MAPK proteins in the kidneys of cisplatin-treated mice.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The MAPK pathway is a key factor in regulating cisplatin-induced kidney damage and inflammation. Based on previous evidence, various biological responses have been associated with the activation of MAPKs, which can activate the MAPK pathway by producing oxidative stress and TNF-α in the kidney tissues [40]. In this study, we showed that there was an increased amount of the phosphorylated MAPK proteins in the kidneys of cisplatin-treated mice.…”
supporting
confidence: 57%
“…Oxidative stress is one of the key factors in the pathogenesis of cisplatin-treated renal injury [40]. Cells express a number of antioxidant enzymes (e.g., SOD, catalase, and GPx) to prevent the cell or tissue damage caused by the expression of antioxidant enzymes, in an attempt to decrease oxidative stress.…”
mentioning
confidence: 99%
“…The MAPK signaling pathways play an important role in regulating inflammation and apoptosis ( Nath, 2006 ; Zmonarski et al, 2019 ). Previous studies have reported that MAPK pathways are activated in cisplatin-induced AKI, and inhibition of MAPK pathways alleviate cisplatin-induced inflammation and apoptosis ( Sahu, Mahesh Kumar & Sistla, 2015 ).…”
Section: Resultsmentioning
confidence: 99%